SYNERGETIC STRATEGIES: CO-CREATION AND ARTIFICIAL INTELLIGENCE IN IMPROVING TRANSLATION SKILLS - Damanik, Lia Agustina (Journal of English Education and Linguistics, 2024)
This study investigates using co-creation strategies and AI tools to improve translation skills among English Education students at STAIN Mandailing Natal. Sixty students shared their experiences with Peer Review, Collaborative Translation Projects, and Computer-Assisted Translation (CAT) Tools. The feedback highlighted areas for effective AI integration. Consequently, researchers proposed using AI for real-time feedback in Peer Review sessions, facilitating communication in collaborative projects with AI project management tools, and enhancing predictive text features in CAT Tools using advanced machine learning. After several months of implementing these methods, a post-test showed significant improvements: accuracy rose by 20%, fluency by 15%, and appropriateness scores by 18%. Confidence levels also increased across all translation aspects. The study shows that integrating AI within co-creation strategies enhances both hard skills (translation abilities) and soft skills (teamwork & confidence), improving overall learning outcomes.